Implementation of Law Number 8 of 1999 concerning Consumer Protection: The Relationship of Beauty Care Products in the City of Parepare - Suarning; Kumalasari, Intan; B, Asfiani; Said, Zainal (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2022)
The implementation of Law Number 8 of 1999 concerning Consumer Protection regarding the sale of Beauty Care Products in the City of Parepare is still not optimal because there are still many dangerous beauty care products found. Of course this results in losses to the consumer. This research uses a normative juridical method, a juridical approach, namely legal research conducted by examining library materials or secondary data as basic materials to be studied by conducting a search on regulations and literature related to the problems studied. The data collection technique uses observation, interviews, and documentation while the data analysis technique used in this study is the data analysis technique used by the researcher using the Miles and Huberman model, that there are three flow of activities, namely data reduction, data presentation, and drawing conclusions or conclusions. verification. The results of this study indicate that: 1) . The position of consumers is considered vulnerable because they cannot be separated from buying and selling activities and often experience fraud that results in losses. So to protect consumers, the government makes regulations on consumer protection Law No. 8 of 1999 which explains the principles of consumer protection, consumer protection goals, consumer rights, and obligations as consumers, 2) Implementation of regulations on selling beauty care products in the city. Parepare has long been in effect, but the reality in the field is not in accordance with the application of the rules because there are still many sellers who trade products that still use ingredients that are quite harmful to health, 3) Review of Islamic Economic Law regarding the sale of beauty care products in Indonesia. the city of Parepare which is not in accordance with existing Islamic law. Because, in the buying and selling process it is not in accordance with the rules contained in the legal conditions of the sale and purchase law, namely Ma'qud Alaih and Syara'.